Herzog's Struggle For Better Mental Quality In Saul Bellow's Herzog: An Individual Psychological Approach - Khikmah, Nur (2004)
This study investigates Herzog's struggle for better mental quality that influences his personality development in Saul Bellow's Herzog viewed from individual psychological approach. Therefore, the aim of this study is to analyze the novel based on individual psychological Approach. This study belongs to a qualitative study. In this method, the writer uses two types of data sources, namely primary and secondary data sources. The primary data source and the object of the study are the novel itself. The writer collects the data from both primary and secondary data sources in sort of document as evidence. The technique of analyzing data is descriptive. Based on the analysis, the writer draws some conclusions as follows: first, Saul Bellow's Herzog tells about a man having unstable psychological condition resulted from unfortunate happenings. This problem causes the major character, Herzog, to struggle for getting better mental quality. Second, the struggle conducted by the major character influences his mental condition that it becomes better than before. The last, that Herzog's struggle for getting better mental quality influences his personality namely from being immature and reckless about women to being wise and mature.